Vol.XV No.1 It's the Microbe that Makes Organic Matter! - University of Minnesota. Agricultural Experiment Station (Minnesota Agricultural Experiment Station, 1957)
microbes, potatoes, junior geese, lambs, winter hardiness in alfalfa, co-ops, ascorbic acid and orange juice and mineral absorption, moisture controls for buildings, ornithosis, pepsin in pig starters, malting quality in barley,
20 pages